2009
DOI: 10.1007/s00264-009-0866-2
|View full text |Cite|
|
Sign up to set email alerts
|

Risk factors in cutout of sliding hip screw in intertrochanteric fractures: an evaluation of 937 patients

Abstract: The aim of this study was designed to assess the risk factors of lag-screw cutout in the treatment of intertrochanteric fracture with a dynamic hip screw (DHS). From 2003 to 2007, 1,150 patients who had acute unilateral intertrochanteric fractures of the femur were enrolled to the study. All fractures were managed by closed reduction and internal fixation with 135°DHS devices. Patient demographics, fracture patterns, reduction and fixation and perioperative course parameters were all recorded. The follow-up pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
160
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(183 citation statements)
references
References 23 publications
6
160
0
4
Order By: Relevance
“…TAD is the only validated clinical outcome that was measured (Baumgaertner et al 1995, Güven et al 2010, Hsueh et al 2010, Andruszkow et al 2012). Baumgaertner et al (1995) demonstrated that a TAD of less than 25 mm was the most important factor to minimize the cut-out rate.…”
Section: Discussionmentioning
confidence: 99%
“…TAD is the only validated clinical outcome that was measured (Baumgaertner et al 1995, Güven et al 2010, Hsueh et al 2010, Andruszkow et al 2012). Baumgaertner et al (1995) demonstrated that a TAD of less than 25 mm was the most important factor to minimize the cut-out rate.…”
Section: Discussionmentioning
confidence: 99%
“…This data was extracted from the existing database of all hip fractures, submitted for audit to the NHFD. 11 patients were excluded because they did not sustain a trochanteric fracture (2), had treatment of a pathological fracture (3) or because of incomplete radiographic data (6). Three observers used a standardised method to measure the TAD, which was defined as the sum of the distance in mm, from the tip of the lag screw to the apex of Abstract Introduction: Fixation of trochanteric femoral neck fractures can be problematic.…”
Section: Methodsmentioning
confidence: 99%
“…The commonest mode of failure of sliding hip screw devices is cut-out, or extrusion, from the femoral head [3][4][5][6]. Position of the lag screw as determined by the TAD has been shown the most important predictive factor in cut-out and this radiographic measurement can be readily determined using published methods [1,3]. In many UK centres, routine follow up in hip fracture patients after fixation does not occur except for intracapsular fractures treated by internal fixation, in whom there is a risk of non-union (20-33%) and avascular necrosis (10-20%) necessitating re-operation [7].…”
Section: Introductionmentioning
confidence: 99%
“….DHS failure rate has been previously reported as 8% -13% [12] but the rate came down to 6.8% according to a more recent study [13]. Previous studies have recommended the essential role of adequate reduction of the fracture, as well as central placement of the lag screw on AP and lateral views of the radiographs and suggested that tip apex distance (TAD) is the most important prediction factor for DHS cut through.…”
Section: Introductionmentioning
confidence: 99%
“…It is important that the technique of screw placement is precise and should ideally be central in the femoral neck, on both anteroposterior and lateral radiographs. Other predictors of cut through of DHS include fracture pattern, patient's age and presence of osteoporosis [13,14]. This present retrospective study determined the epidemiological pattern, care, complications and functional outcome of pertrochanteric fractures following treatment with dynamic hip screw.…”
Section: Introductionmentioning
confidence: 99%